ANALISIS IMPLEMENTASI MODEL PEMBELAJARAN BLENDED LEARNING UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR PADA TEMA MENUJU MASYARAKAT SEJAHTERA SISWA KELAS VI ( (Studi Kasus di SD Negeri 1 Kemujan pada Era Covid-19 Tahun Ajaran 2020/ - Sari, Apriliani Indah; Rokhmaniyah, Rokhmaniyah; Susiani, Tri Saptuti (Universitas Sebelas Maret, 2021)
The study aimed to describe the implementation of blended learning model to improve independent learning in theme ‘Towards a Prosperous Community’ for sixth grade students of SD Negeri 1 Kemujan in the Covid-19 era. It was qualitative approach with a case study research method. Data collection techniques were observation, interview, and document study. Data analysis was according to Miles and Huberman included data reduction, data presentation, and verification. The results showed that the implementation of blended learning model to improve independent learning for sixth grade students of SD Negeri 1 Kemujan in the Covid-19 era was good. The planning of blended learning was good included creating learning schedules, compiling lesson plans, choosing types of blended learning model, preparing learning materials, tools/media, face-to-face and online learning resources, and implementing health protocol of Covid-19 during face-to-face learning. The implementation of blended learning was sufficient included seeking of information, acquisition of information, and synthesizing of knowledge. The evaluation of blended learning was good in improving independent learning. It concludes that blended learning to improve independent learning meets the indicators.